Grazing exclusion-induced changes in soil fungal communities in a highly desertified Brazilian dryland - Silva, Danilo F.; Mazza Rodrigues, Jorge L.; Erikson, Christian; Silva, Antonio M.M.; Huang, Laibin; Araujo, Victor L.V.P.; Matteoli, Filipe P. [UNESP]; Mendes, Lucas W.; Araujo, Ademir S.F.; Pereira, Arthur P.A.; Melo, Vania M.M.; Cardoso, Elke J.B.N. (Elsevier, 2024)
Soil desertification poses a critical ecological challenge in arid and semiarid climates worldwide, leading to decreased soil productivity due to the disruption of essential microbial community processes. Fungi, as one of the most important soil microbial communities, play a crucial role in enhancing nutrient and water uptake by plants through mycorrhizal associations. However, the impact of overgrazing-induced desertification on fungal community structure, particularly in the Caatinga biome of semiarid regions, remains unclear. In this study, we assessed the changes in both the total fungal community and the arbuscular mycorrhizal fungal community (AMF) across 1. Natural vegetation (native), 2. Grazing exclusion (20 years) (restored), and 3. affected by overgrazing-induced degradation (degraded) scenarios. Our assessment, conducted during both the dry and rainy seasons in Irauçuba, Ceará, utilized Internal Transcribed Spacer (ITS) gene sequencing via Illumina® platform. Our findings highlighted the significant roles of the AMF families Glomeraceae (∼71% of the total sequences) and Acaulosporaceae (∼14% of the total sequences) as potential key taxa in mitigating climate change within dryland areas. Moreover, we identified the orders Pleosporales (∼35% of the total sequences) and Capnodiales (∼21% of the total sequences) as the most abundant soil fungal communities in the Caatinga biome. The structure of the total fungal community differed when comparing native and restored areas to degraded areas. Total fungal communities from native and restored areas clustered together, suggesting that grazing exclusion has the potential to improve soil properties and recover fungal community structure amid global climate change challenges.
Keywords: Drylands; Fungal communities; Mycorrhizal symbiosis; Soil degradation